PENGARUH KOMPETENSI APARATUR PENGELOLAAN DANA DESA, PERAN PERANGKAT DESA DAN SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS - Ayu Lia Juwitha Dewi; Ni Komang Sumadi; Ni Ketut Muliati (UNHI Press, 2022)
Accountability is an important element that must be maintained in the organization. openness will bring a healthy organization. The writings compiled in this thesis are made to see things that can cause accountability to appear higher. As for the elements studied, namely the Competence of the Village Fund Management Apparatus, the Role of the Village Apparatus, and Human Resources. The number of samples in this study was 162 people who were determined by purposive sampling technique and tested using multiple linear regression analysis techniques. The research found that the bottom line is that accountability will experience an increase when the competence of the village fund management apparatus, the role of village officials, and human resources is maintained and improved.